SPATIAL AND TEMPORAL DISTRIBUTION STUDIES CONTENTS OF BOD, TSS AND DO WATER RIVER STONE ARAU PADANG CITY 2018 - Burhan Muslim (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2020)
Abstract Biological Oxygen Demand (BOD), Total Suspended Solid (TSS) and Dissolved Oxygen (DO) are indicators of water quality in water bodies. Non-polluted water has low BOD and TSS levels and high DO. Changes in these three parameters indicate a change in quality. This study aims to look at variations in the levels of BOD, TSS and DO spatially and temporarily in Batang Arau River, Padang City in 2018. The study was conducted by observing three stations, namely in the upstream, middle and downstream and in the morning and evening. The results showed that BOD and TSS levels tended to increase from upstream to downstream, while DO was the opposite. Temporar variation shows that BOD and TSS levels are low in the morning and increase during the day and evening, while DO is the opposite. Key word: Biological Oxygen Deman, Total Suspended Solid, Dissolved Oxygen Abstrak Kbutuhan Oksigen Biologis (BOD), Total Suspended Solid (TSS) dan Dissolved Oxygen (DO) adalah indikator kualitas air dalam badan air. Air yang tidak tercemar memiliki kadar BOD dan TSS yang rendah serta DO yang tinggi. Perubahan dalam ketiga parameter ini menunjukkan perubahan kualitas. Penelitian ini bertujuan untuk melihat variasi kadar BOD, TSS dan DO secara spasial dan temporer di Sungai Batang Arau, Kota Padang pada tahun 2018. Penelitian ini dilakukan dengan mengamati tiga stasiun, yaitu di hulu, tengah dan hilir dan pada pagi hari, dan malam. Hasil penelitian menunjukkan bahwa tingkat BOD dan TSS cenderung meningkat dari hulu ke hilir, sedangkan DO adalah sebaliknya. Variasi temporer menunjukkan bahwa tingkat BOD dan TSS rendah di pagi hari dan meningkat pada siang dan malam hari, sedangkan DO adalah sebaliknya.